An injectable cross-linked agarose composite hydrogel implant and a method of making the same

CN122894553APending Publication Date: 2026-10-13SHANGHAI HUABAN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219627.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明是为了克服琼脂糖物理凝胶存在制粒工艺难度高、推注性能不佳等问题,提高琼脂糖凝胶粒径均匀度,与基底液融合,使制备的琼脂糖复合凝胶质地丝柔,均匀细腻,具有良好的粘弹性能、内聚力和推注性能,提高患者治疗的舒适性、安全性和有效性

Benefits of technology

本发明通过化学交联、温度控制的简单工艺,可以得到具有良好生物相容性,无免疫原性,低毒性,均匀细腻,具有良好的粘弹性能和内聚力、良好推注性能的琼脂糖复合凝胶,作为长效填充剂使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894553A_ABST
    Figure CN122894553A_ABST
Patent Text Reader

Abstract

The application discloses an injectable cross-linked agarose composite hydrogel implant and a preparation method thereof, and belongs to the technical field of biomedical materials, and comprises the following steps: S1, agarose powder is placed in water, physiological saline, a phosphate buffer solution or a Tris solution, is dissolved at 55-125 DEG C for 30 min-10 h, a clear and transparent agarose solution is obtained, and the temperature is reduced to 25-75 DEG C for standby; S2, composite components are dissolved in an alkaline solution, and stirring is conducted until the alkaline solution is completely dissolved to obtain a solution I; S3, the solution I is added to the agarose solution after temperature reduction, and stirring is conducted until the solution I is uniformly mixed to obtain a solution II; S4, a cross-linking system solution is added to the solution II, and stirring is conducted until the cross-linking system solution is uniformly mixed to obtain a solution III; S5, the solution III is placed at 20-60 DEG C for 0.1-72 h, and an agarose composite gel is obtained; S6, the agarose composite gel is treated to be neutral, is homogenized, is mixed with a matrix solution to obtain an injectable agarose composite gel implant, and terminal sterilization is conducted after filling. The application has better compression mechanical properties, and the support property of facial filling is more durable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, and relates to an injectable cross-linked agarose composite hydrogel implant and its preparation method. Background Technology

[0002] With the aging population, the demand for improving facial wrinkles and sagging skin is particularly prominent among middle-aged and elderly people. Meanwhile, the core customer group aged 25-40 is shifting its needs from simple wrinkle removal to natural aesthetics and personalized shaping. Facial filler injections, with their advantages of short recovery periods, relatively low risks, and immediate results, align with current consumer preferences for "minimally invasive beauty enhancement" and are therefore highly favored. Currently, the facial implant market is mainly dominated by hyaluronic acid gel, but hyaluronic acid gel has a rapid degradation rate (usually 6-12 months), requires repeated injections, and its high water absorption poses a risk of facial "blurring." Collagen products, on the other hand, face risks of immunogenicity and transmission of animal-derived viruses. Therefore, finding safe and long-lasting effective filler materials is a crucial issue in the field of cosmetic surgery.

[0003] Agarose, extracted from natural seaweed, has a chemical structure consisting of repeating β-D-galactose and 3,6-dehydrated α-L-galactose residues, similar to the structure of natural polysaccharides (such as glycosaminoglycans) in human tissues. It is a naturally linear polysaccharide with good biocompatibility and does not trigger a strong immune rejection response, a property similar to hyaluronic acid. However, unlike hyaluronic acid's tendency to absorb large amounts of water, agarose does not significantly absorb water during gelation. However, agarose physical gels only have water-retention properties and poor hydrophilicity. Constructing agarose-based composite gel networks with other hydrophilic molecules can improve the hydrophilicity and biocompatibility of agarose gels; however, the hydrophilicity of the composite gel is limited, so there is no potential risk of excessive water absorption and swelling in vivo. Another significant advantage of agarose is its almost non-charged groups, thus rarely causing denaturation or adsorption of sensitive biomolecules, exhibiting relative stability in vivo. These properties not only make it a novel physical site-occupying material but also achieve a "what you see is what you get" therapeutic effect.

[0004] Facial fillers need to maintain low viscosity during injection to pass through fine needles (27-30G), and simultaneously need to rapidly develop sufficient mechanical strength after implantation to support soft tissue. High-purity agarose gel is obtained directly through a high-temperature dissolution-cooling solidification method. This gel has high strength, cannot be directly injected using a syringe, and is difficult to granulate through sieving. Summary of the Invention

[0005] This invention aims to overcome the problems of difficult granulation and poor injection performance of agarose physical gels, improve the particle size uniformity of agarose gel, and enhance its fusion with the base liquid. The resulting agarose composite gel has a silky, uniform, and delicate texture with good viscoelastic properties, cohesiveness, and injection performance, thereby improving patient comfort, safety, and effectiveness. This invention strives to overcome the biases in existing technologies and explore a simpler, more effective, and safer injectable agarose composite gel implant and its preparation method.

[0006] The technical solution adopted by this invention to achieve its purpose is as follows: A method for preparing an injectable cross-linked agarose composite hydrogel implant includes the following steps: S1. Place agarose powder in water, physiological saline, phosphate buffer (pH 7.2-7.4), or Tris solution (pH 7.2-7.4). The mass ratio of agarose powder to water, physiological saline, phosphate buffer (pH 7.2-7.4), or Tris solution (pH 7.2-7.4) is 0.5:100-10:100. Dissolve at 55-125℃ for 30 min-10 h to obtain a clear and transparent agarose solution. Cool to 25-75℃ and set aside for later use. S2. Dissolve the composite components in an alkaline solution and stir until completely dissolved to obtain solution I; S3. Add solution I obtained in step S2 to the agarose solution after cooling in step S1, stir well, and obtain solution II; S4. Add the cross-linking system solution to solution II obtained in step S3, stir until homogeneous, and obtain solution III; S5. Place the solution III obtained in step S4 at 20-60℃ for 0.1-72 h to obtain agarose composite gel; S6. After the agarose composite gel obtained in step S5 is neutralized and homogenized, it is mixed with the matrix solution to obtain an injectable agarose composite gel implant, which is then filled and terminally sterilized.

[0007] Furthermore, the composite components are selected from one or more of the following: sodium hyaluronate, chondroitin sulfate, glycerin, mannitol, dextran, β-cyclodextrin, amylopectin, methylcellulose, carboxymethylcellulose, ethylcellulose, hydroxypropyl methylcellulose, chitosan, chitin, alginate, xanthan gum, gum arabic, gelatin, collagen, silk fibroin, polyacrylamide, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternium salt, and polyethylene glycol.

[0008] Furthermore, the mass ratio of the composite component to the agarose powder is 0.1:100-20:100.

[0009] Furthermore, the alkaline solution is selected from any one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, and sodium carbonate solution; the mass percentage concentration of the alkaline solution is 0.1-15%.

[0010] Furthermore, the crosslinking system solution is composed of a mixture of a first component and a second component; The first component includes one or more of 1,4-butanediol diglycidyl ether, epichlorohydrin, poly(propylene glycol) diglycidyl ether, poly(butanediol) diglycidyl ether, polyglycerol polyglycidyl ether, glycerol diglycidyl ether, triethylene diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether. The second component includes one or more of anhydrous ethanol, isopropanol, n-butanol, ethylene glycol dimethyl ether, dioxane, acetone, methyl ethyl ketone, and cyclohexanone.

[0011] Furthermore, the molar ratio of the first component to agarose (calculated based on an agarose molecule containing two pyran rings with a molecular mass of 315) is selected from 0.5% to 60%, and the ratio of the first component to the second component is 10% to 100%.

[0012] Further, the matrix solution is selected from water, phosphate buffer (pH 7.2-7.4), physiological saline, Tris solution (pH 7.2-7.4), or a solution prepared from one or more of the following: sodium hyaluronate, chondroitin sulfate, glycerol, mannitol, dextran, β-cyclodextrin, amylopectin, methylcellulose, carboxymethylcellulose, ethylcellulose, hydroxypropyl methylcellulose, chitosan, chitin, alginate, xanthan gum, gum arabic, gelatin, collagen, silk fibroin, polyacrylamide, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternium salt, and polyethylene glycol, and one of these solutions mixed with water, phosphate buffer (pH 7.2-7.4), physiological saline, and Tris solution (pH 7.2-7.4); wherein, except for a fixed ratio of pure water, phosphate buffer (pH 7.2-7.4), physiological saline, and Tris solution (pH 7.2-7.4), the mass percentage concentration of the matrix solution is selected from 0.1~ 10%.

[0013] Furthermore, the mass ratio of the matrix solution to the agarose gel is selected from 1:100 to 1:1.

[0014] The injectable cross-linked agarose composite hydrogel implant is prepared by the method described above.

[0015] Application of an injectable cross-linked agarose composite hydrogel implant in the preparation of medical aesthetic injectable products.

[0016] The beneficial effects of this invention are: This invention utilizes a simple process involving chemical cross-linking and temperature control to obtain an agarose composite gel with good biocompatibility, no immunogenicity, low toxicity, uniform and fine texture, good viscoelastic properties and cohesiveness, and good injection performance, which can be used as a long-lasting filler.

[0017] This invention overcomes the biases in existing technologies by chemically cross-linking an agarose composite solution to obtain an injectable agarose composite gel implant suitable for facial filling, avoiding the problems of difficult granulation and poor injection performance associated with physical agarose gels. Utilizing the principle of "like dissolves like," the weakly polar second component not only dissolves the first component well but is also miscible with the aqueous solution, significantly improving the dispersion of the first component in water. This helps improve cross-linking uniformity and ensures process and product quality stability. Homogenization improves the particle size uniformity of the agarose composite gel, allowing it to fuse with the base solution. The prepared agarose composite gel has a silky, uniform, and delicate texture with good viscoelastic properties, cohesion, and injection performance, improving user comfort, safety, and effectiveness. The agarose composite gel implant has a high G'' (viscosity modulus), indicating good gel viscosity. Therefore, when applied to facial filling, a high viscosity modulus gel will exhibit better integration with surrounding tissues and is less prone to displacement. ® VL has been used in over 40 countries and regions worldwide for more than 16 years, demonstrating excellent biocompatibility and clinical safety. This indicates that agarose, as a natural polysaccharide material, possesses excellent biocompatibility and exhibits low cytotoxicity, sensitization, and immunogenicity, making it a relatively safe choice for facial volume restoration and contouring. The composite gel of this invention uses agarose as the main material, possessing advantages such as high plasticity and good injectability, and can be used as a long-lasting filler. The preparation process of this invention involves few steps, simple and controllable process parameters, and reliable and stable product quality, making it suitable for large-scale industrial production. Attached Figure Description

[0018] Figure 1 The results are the gel compression modulus test results for Example 1 and Comparative Example 1.

[0019] Figure 2 The rheological test results are for the implants obtained in Examples 2, 3, 4 and 5 and Comparative Example 2.

[0020] Figure 3 Microscopic images and particle sizes of the implants obtained in Examples 2, 3, 4 and 5 and Comparative Example 2.

[0021] Figure 4The results of the extrusion force test are for the implants obtained in Examples 2, 3, 4 and 5 and Comparative Example 2.

[0022] Figure 5 The images show the particle size distribution and actual particle size distribution of Example 5. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0024] Example 1

[0025] Preparation of agarose complex gel: 5.25 g of agarose powder was added to 124 g of ultrapure water and dissolved at 105 °C for 50 min to obtain a clear and transparent agarose solution. The agarose solution was cooled to 60 °C, and 11.15 g of sodium hydroxide solution containing 0.26 g of sodium hyaluronate powder was added and stirred until homogeneous. The final mass percentage concentration of sodium hydroxide was 3.6%. 2.1 g of 1,4-butanediol glycidyl ether and 7.5 g of anhydrous ethanol were mixed evenly and added to the agarose composite solution, and stirred for 20 min. Crosslinking was performed at 60 °C for 16 h, and after treatment to neutrality, the agarose composite gel was obtained.

[0026] Example 2

[0027] Preparation of injectable agarose composite gel implant: 3.7g of agarose powder was added to 67.67g of ultrapure water and dissolved at 121℃ for 30min to obtain a clear and transparent agarose solution. The agarose solution was cooled to 55℃, and 22.78g of potassium hydroxide solution containing 0.37g of dextran was added and stirred until homogeneous. The final mass percentage concentration of potassium hydroxide was 1.2%. 1.85g of 1,4-butanediol glycidyl ether and 2g of isopropanol were mixed evenly and added to the agarose composite solution, and stirred for 20min. Crosslinking was carried out at 55℃ for 6h. After treatment to neutrality, homogenization was performed through an 80-150 mesh sieve. 50g of 3% sodium hyaluronate solution was added to 50g of agarose composite gel and dispersed evenly. The gel was then filled into pre-filled syringes and sterilized by moist heat to obtain the injectable crosslinked agarose composite gel implant.

[0028] Example 3

[0029] Preparation of injectable agarose composite gel implant: 2.5g of agarose powder was added to 71.97g of ultrapure water and dissolved at 115℃ for 60min to obtain a clear and transparent agarose solution. The agarose solution was cooled to 55℃, and 22.78g of sodium hydroxide solution containing 0.45g of sodium hyaluronate was added and stirred until homogeneous. The final mass percentage concentration of sodium hydroxide was 1.2%. 0.75g of 1,4-butanediol glycidyl ether was mixed with 2g of anhydrous ethanol and added to the agarose composite solution, and stirred for 20min. Crosslinking was performed at 45℃ for 16h. After treatment to neutrality, homogenization was performed through a 50-100 mesh sieve. 30g of 4% sodium hyaluronate solution was added to 60g of agarose composite gel and dispersed evenly. The gel was then filled into pre-filled syringes and sterilized by moist heat to obtain the injectable crosslinked agarose composite gel implant.

[0030] Example 4

[0031] Preparation of injectable agarose composite gel implant: 5.0 g of agarose powder was added to 72.25 g of ultrapure water and dissolved at 95 °C for 70 min to obtain a clear and transparent agarose solution. The agarose solution was cooled to 50 °C, and 18.0 g of sodium hydroxide solution containing 0.4 g of dextran was added and stirred until homogeneous. The final mass percentage concentration of sodium hydroxide was 1.8%. 1.75 g of 1,4-butanediol glycidyl ether and 3.0 g of isopropanol were mixed evenly and added to the agarose composite solution, and stirred for 20 min. Crosslinking was carried out at 50 °C for 6 h. After treatment to neutrality, homogenization was performed through a 90-150 mesh sieve. 10 g of 2% carboxymethyl cellulose solution was added to 50 g of agarose composite gel particles and dispersed evenly. The gel was then filled into pre-filled syringes and sterilized by moist heat to obtain the injectable crosslinked agarose composite gel implant.

[0032] Example 5

[0033] Preparation of injectable agarose composite gel implant: The agarose composite gel obtained in Example 1 was homogenized through a 100-200 mesh sieve to obtain agarose composite gel particles. 10g of 1% hydroxypropyl methylcellulose solution was added to 40g of agarose composite gel particles and dispersed evenly. The gel was then filled into pre-filled syringes and sterilized by moist heat to obtain injectable cross-linked agarose composite gel implants.

[0034] Comparative Example 1 Preparation of agarose physical gel: Add 5.25g of agarose powder to 144.75g of ultrapure water and dissolve at 105℃ for 30min to obtain a clear and transparent agarose solution. Cool to room temperature to obtain an agarose physical gel.

[0035] Comparative Example 2 Commercially available product "Agarose Facial Injectable Filler" ALGENESS ® VL 1.5%.

[0036] Performance Testing and Results Analysis Compression modulus test The compressive modulus of the gels prepared in Example 1 and Comparative Example 1 were tested.

[0037] The test conditions are as follows: Instrument Name: Universal Testing Machine; Test temperature: room temperature; Test mode: Compression test; Test speed: 1 mm / min; Test sample size: a cylinder with a diameter of 26 mm and a height of 10 mm.

[0038] The test results are as follows Figure 1 As shown: In Example 1 and Comparative Example 1, the agarose mass percentage concentration was the same, 3.5%. As can be seen from the figure, the compressive modulus of Example 1 was approximately 0.4 MPa, significantly greater than that of Comparative Example 1. Example 1 exhibited superior elastic recovery, which helps maintain the shaping effect after injection.

[0039] Rheological testing The injectable agarose composite gel implants prepared in Examples 2, 3, 4, and 5 were subjected to rheological (viscoelastic) tests compared with Comparative Example 2. The viscoelasticity of injectable gels is a core mechanical indicator determining the durability, shaping ability, biocompatibility, and safety of their facial filling effects. Revealing the rheological properties of these implant products helps guide clinicians in combining products with actual cosmetic needs, thereby selecting implants with appropriate rheological properties to achieve long-lasting, natural, and ideal aesthetic results.

[0040] The test conditions are as follows: Instrument Name: Rheometer; Test fixture: 25mm flat plate; clearance: 1mm; Test temperature: 25℃; Test description: Oscillation frequency scanning was performed at frequencies of 0.1Hz-10Hz and a shear strain of 0.1%.

[0041] The test results are as follows Figure 2 As shown: As shown in the figure, the four groups of products in Examples 2, 3, 4, and 5 are all high G' (elastic modulus) gels, significantly higher than that of Comparative Example 2. This indicates that the gel is not easily deformed under external force and can quickly return to its original shape after the external force is removed. As a filler, it can maintain a firm shape for a long time. The high G (viscous modulus) values ​​of the products in Example 4 indicate that the gel has good viscosity and extensibility, can integrate well with surrounding tissues, and is not prone to causing a foreign body sensation. tanδ is the ratio of G" to G', which measures the elasticity and viscosity of the filler and determines the "applicable scenarios" of the filler. The fillers prepared in this invention all have tanδ values ​​less than 1, indicating that they are suitable for scenarios requiring strong support. This invention can control the rheological properties of the composite gel through the cross-linking process and formulation ratio to meet the aesthetic needs of different facial areas of patients.

[0042] Morphology test The injectable agarose composite gel implants prepared in Examples 2, 3, 4 and 5 above were subjected to morphological tests compared with Comparative Example 2.

[0043] The test conditions are as follows: Instrument Name: Optical Microscope; Test description: Take an appropriate amount of gel, add 0.1% toluidine blue staining solution, mix well, and observe and photograph under a microscope.

[0044] Particle size testing The particle size of the injectable agarose composite gel implants prepared in Examples 2, 3, 4 and 5 above, and Comparative Example 2 was tested.

[0045] The test conditions are as follows: Instrument Name: Laser Particle Size Analyzer; Test description: Take an appropriate amount of gel, add it to the dispersion chamber, and conduct the test.

[0046] The morphology and particle size test results are as follows Figure 3 As shown: Comparative Example 2 has a particle size D90 of less than 200 μm. Examples 2, 3, 4 and 5 obtained uniform injectable agarose composite gels with different particle sizes through different homogenization processes.

[0047] Push force test The injectable agarose composite gel implants prepared in Examples 2, 3, 4 and 5 above, and Comparative Example 2 were subjected to extrusion force tests.

[0048] The testing conditions are as follows: universal testing machine; Test temperature: room temperature; Test sample specifications: 1 mL of product from Examples 2, 3, 4 and 5 was used with a 27 G ETW syringe, and 1 mL of product from Example 2 was used with a 30 G × 1 / 2" syringe.

[0049] Pushing speed: 30mm / min, record the pushing force value.

[0050] The test results are as follows Figure 4 As shown: As can be seen from the figure, the average pushing force of the four groups of products in Examples 2, 3, 4, and 5 is in the range of 2-10N, which is significantly less than the average pushing force of Comparative Example 2. The filler prepared by this invention meets the standard requirements for injection fillers, and the injection curve has very small fluctuations, is smooth, and exhibits excellent injectability.

[0051] from Figure 5 As can be seen from the results, the injectable agarose composite gel implant prepared in Example 5 has good particle size uniformity, silky texture, and is uniform and delicate.

[0052] Finally, it should be noted that the above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit them. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention.

Claims

1. A method for preparing an injectable cross-linked agarose composite hydrogel implant, characterized in that, Includes the following steps: S1. Place agarose powder in water, physiological saline, phosphate buffer or Tris solution and dissolve it at 55-125℃ for 30 min-10 h to obtain a clear and transparent agarose solution. Cool it down to 25-75℃ and set aside. S2. Dissolve the composite components in an alkaline solution and stir until completely dissolved to obtain solution I; S3. Add solution I obtained in step S2 to the agarose solution after cooling in step S1, stir well, and obtain solution II; S4. Add the cross-linking system solution to solution II obtained in step S3, stir until homogeneous, and obtain solution III; S5. Place the solution III obtained in step S4 at 20-60℃ for 0.1-72 h to obtain agarose composite gel; S6. After the agarose composite gel obtained in step S5 is neutralized and homogenized, it is mixed with the matrix solution to obtain an injectable agarose composite gel implant, which is then filled and terminally sterilized.

2. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The composite components are selected from one or more of the following: sodium hyaluronate, chondroitin sulfate, glycerin, mannitol, dextran, β-cyclodextrin, amylopectin, methylcellulose, carboxymethylcellulose, ethylcellulose, hydroxypropyl methylcellulose, chitosan, chitin, alginate, xanthan gum, gum arabic, gelatin, collagen, silk fibroin, polyacrylamide, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternium salt, and polyethylene glycol.

3. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The mass ratio of the composite component to agarose powder is 0.1:100-20:

100.

4. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The alkaline solution is selected from any one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, and sodium carbonate solution; the mass percentage concentration of the alkaline solution is 0.1-15%.

5. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The crosslinking system solution is composed of a mixture of a first component and a second component; The first component comprises one or more of 1,4-butanediol diglycidyl ether, epichlorohydrin, poly(propylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, poly(butanediol) diglycidyl ether, polyglycerol polyglycidyl ether, glycerol diglycidyl ether, triethylene diglycidyl ether, trimethylolpropane triglycidyl ether, ethylene diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether. The second component includes one or more of anhydrous ethanol, isopropanol, n-butanol, ethylene glycol dimethyl ether, dioxane, acetone, methyl ethyl ketone, and cyclohexanone.

6. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 5, characterized in that, The molar ratio of the first component to agarose is selected from 0.5% to 60%, and the ratio of the first component to the second component is 10% to 100%.

7. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The matrix solution is selected from water, phosphate buffer, physiological saline, Tris solution, or a solution prepared from one or more of the following: sodium hyaluronate, chondroitin sulfate, glycerol, mannitol, dextran, β-cyclodextrin, amylopectin, methylcellulose, carboxymethylcellulose, ethylcellulose, hydroxypropyl methylcellulose, chitosan, chitin, alginate, xanthan gum, gum arabic, gelatin, collagen, silk fibroin, polyacrylamide, polyacrylic acid, polyvinylpyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternium salt, and polyethylene glycol, and one of the following: water, phosphate buffer, physiological saline, and Tris solution.

8. The method for preparing an injectable cross-linked agarose composite hydrogel implant according to claim 1, characterized in that, The mass ratio of the matrix solution to the agarose gel is selected from 1:100 to 1:

1.

9. The injectable cross-linked agarose composite hydrogel implant prepared according to the method described in claim 1.

10. The application of the injectable cross-linked agarose composite hydrogel implant according to claim 9 in the preparation of medical aesthetic injectable products.